2014
DOI: 10.1136/bmjopen-2014-005091
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial. Comparison Of iNfliximab and ciclosporin in STeroid Resistant Ulcerative Colitis: Trial design and protocol (CONSTRUCT)

Abstract: IntroductionMany patients with ulcerative colitis (UC) present with acute exacerbations needing hospital admission. Treatment includes intravenous steroids but up to 40% of patients do not respond and require emergency colectomy. Mortality following emergency colectomy has fallen, but 10% of patients still die within 3 months of surgery. Infliximab and ciclosporin, both immunosuppressive drugs, offer hope for treating steroid-resistant UC as there is evidence of their short-term effectiveness. As there is litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…We did a mixed methods, open-label, parallel-group, pragmatic randomised trial in 52 district general and teaching hospitals across England, Scotland, and Wales 10 . Potential participants were identified after unscheduled admission with severe ulcerative colitis.…”
Section: Methodsmentioning
confidence: 99%
“…We did a mixed methods, open-label, parallel-group, pragmatic randomised trial in 52 district general and teaching hospitals across England, Scotland, and Wales 10 . Potential participants were identified after unscheduled admission with severe ulcerative colitis.…”
Section: Methodsmentioning
confidence: 99%
“…54 However, in 2012 slower recruitment than predicted led us to seek agreement from the Trial Steering Committee (TSC), Data Monitoring and Ethics Committee (DMEC) and Health Technology Assessment (HTA) programme to revise the primary outcome and reduce the analysable sample size to 250. We also proposed to analyse the area under the curve (AUC) of scores on the CUCQ collected every 6 months up to 3 years from randomisation; and to include participants who had undergone colectomy by developing and validating a post-colectomy extension to the CUCQ, which we termed the Crohn's and Ulcerative Colitis Questionnaire with post-colectomy extension (CUCQ+).…”
Section: Sample Size and Powermentioning
confidence: 99%
“…unpredictable, more cumbersome) (54,66) that infliximab is seen as better rightly or wrongly (144, 146) necessarily know cic (211,214)…”
Section: Consultants' Views On Nurses' Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic evaluation component was subcontracted to the Health Economics and Policy Research Unit, University of South Wales. The protocol and the results of the trial have been reported by Seagrove et al . and Williams et al .…”
Section: Introductionmentioning
confidence: 99%